Artful persuasion : how to command attention, change minds, and influence people - Mills, Harry, 1950- (American Management Association, 2000)
Peels away the mystery that surrounds the psychology of influence and reveals how the world's most persuasive politicians, advertisers, salespeople, and spin doctors work their magic. Case studies in human behavior, examples of masterful persuaders such as Churchill and Lincoln, and step-by-step guidelines help readers put the power of persuasion to work.